Central extracorporeal circulatory life support (cECLS) in selected patients with critical cardiogenic shock - Schmack, Leonie; Schmack, Bastian; Papathanasiou, Maria; Al-Rashid, Fadi; Weymann, Alexander; Pizanis, Nikolaus; Kamler, Markus; Ruhparwar, Arjang; Rassaf, Tienush; Luedike, Peter (Frontiers in Cardiovascular Medicine, 2023)
Background Percutaneous extracorporeal life support (pECLS) is increasingly applied in cardiogenic shock (CS) despite a lack of evidence from randomized trials. The in-hospital mortality rate of pECLS still reaches up to 60%, while vascular access site complications remain a shortcoming. Surgical approaches with central cannulation for ECLS (cELCS) have emerged as a bail-out option. To date, no systematic approach exists that allows a definition of inclusion or exclusion criteria for cECLS. Methods and results This single-center, retrospective, case-control study includes all patients fulfilling criteria for CS at the West German Heart and Vascular Center Essen/Germany between 2015 and 2020 who underwent cECLS (n = 58), excluding post-cardiotomy patients. Seventeen patients received cECLS (29.3%) as a first-line treatment strategy and 41 patients as a second-line strategy (70.7%). The main complications leading to the use of cECLS as a second-line strategy were limb ischemia (32.8%) and ongoing insufficient hemodynamic support (27.6%). The first-line cECLS cohort showed a 30-day mortality rate of 53.3% that was constant during follow-up. The 30-day mortality rate of secondary cECLS candidates was 69.8% and the rate at 3 and 6 months was 79.1%. Younger patients (<55 years) were more likely to exhibit survival benefit with cECLS (p = 0.043). Conclusion Surgical cECLS in CS is a feasible therapy for highly selected patients with hemodynamic instability, vascular complications, or peripheral access site limitations as complementary strategy in experienced centers.